Comparing undesirable behaviours between ‘designer’ Poodle-cross dogs and their purebred progenitor breeds - Gina T. Bryson; Dan G. O'Neill; Zoe Belshaw; Claire L. Brand; Rowena M. A. Packer (PLoS ONE, 2026)
Designer-crossbreed dogs (deliberate cross-breeding between two or more pure breeds) are exploding in popularity, often driven by beliefs that they commonly exhibit desirable behaviours such as being easy to train or being good with children, despite minimal supporting evidence. This study aimed to fill this gap by comparing Canine Behavioural Assessment and Research Questionnaire (C-BARQ) scores between the three most common designer-crossbreeds in the UK and their relevant progenitor breeds. C-BARQ behaviour data for all 12 sub-scales were collected in March 2023 via an online questionnaire of owners of Cockapoo, Labradoodle, Cavapoo, Cocker Spaniel, Labrador Retriever, Cavalier King Charles Spaniel and Poodle dogs acquired aged ≤16 weeks from 1 st January 2019. C-BARQ scores were analysed using multivariable linear modelling. Valid responses were received representing 9,402 dogs. From 72 behavioural comparisons overall (3 designer-crossbreeds x 2 progenitors x 12 C-BARQ scales), designer-crossbreeds overall exhibited more undesirable behaviours than a progenitor breed in 44.4% comparisons and fewer undesirable behaviours in 9.7% comparisons, with no differences detected for the remaining 45.8%. Cockapoos displayed the most undesirable behaviours of the three designer crossbreeds, and differed from Cocker Spaniels and Poodles in 16/24 comparisons, scoring worse for all 16. Cavapoos differed from Cavalier King Charles Spaniels and Poodles in 12/24 comparisons, scoring worse in 11. In contrast, Labradoodles differed from Labrador Retrievers and Poodles in 11/24 comparisons, scoring worse than their progenitors in five behaviours, but better in six. These findings suggest notable behavioural differences between designer-crossbreeds versus their progenitor breeds, with Cockapoos and Cavapoos in particular scoring worse. Wider awareness by prospective owners of these potential issues around undesirable behavioural traits could avoid misbelief-driven acquisitions (e.g., designer-crossbreeds require minimal training, or are particularly suited to households with children) that risk public health (e.g., elevated dog bite risks) and relinquishment due to unmet expectations.